Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1093/jmt/43.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preferred Music to Reduce Emotional Distress and Symptom Activity During Radiation Therapy

Abstract: Music therapy has decreased anxiety levels in many medical settings. This randomized clinical trial examined the effectiveness of a music listening intervention, delivered by a board-certified music therapist, in patients undergoing curative radiation therapy (RT). Emotional distress (anxiety, depression, and treatment-related distress) and symptoms (fatigue and pain) were measured at baseline, mid-treatment, and end of treatment in 63 patients undergoing RT. Although patients who listened to self-selected mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 0 publications
4
122
0
12
Order By: Relevance
“…Age, culture, and socioeconomic status affect the way people respond to music (Dunn, 2004;Krout, 2007). In this study the participants chose what they considered to be the most relaxing type of music for them, following previous studies indicating the efficacy of patient-selected music in perioperative periods (Kulkarni et al, 2002;Clark et al, 2006;Mitchell and MacDonald, 2006). In general, it has been shown that music chosen by a subject tends to have the most self beneficial effects on relaxation and stress reduction (Siedliecki and Good, 2006;Pelletier, 2004;Krout, 2007).…”
Section: Interventionmentioning
confidence: 98%
“…Age, culture, and socioeconomic status affect the way people respond to music (Dunn, 2004;Krout, 2007). In this study the participants chose what they considered to be the most relaxing type of music for them, following previous studies indicating the efficacy of patient-selected music in perioperative periods (Kulkarni et al, 2002;Clark et al, 2006;Mitchell and MacDonald, 2006). In general, it has been shown that music chosen by a subject tends to have the most self beneficial effects on relaxation and stress reduction (Siedliecki and Good, 2006;Pelletier, 2004;Krout, 2007).…”
Section: Interventionmentioning
confidence: 98%
“…123 In a randomized trial of cancer patients who were receiving radiation therapy (n 5 63), nonsignificant trends in stress reduction were observed in the music condition when compared with controls who did not receive music. 124 Significant results were seen in a randomized clinical trial (n 5 80) where terminally ill cancer patients who were receiving hospice care in their homes were assigned either to a music therapy intervention or to usual hospice care. 125 In that study, those who received repeated sessions of music therapy showed significant improvement in qualityof-life scores, whereas those not receiving music therapy showed decreased quality-of-life scores.…”
Section: Music Therapymentioning
confidence: 99%
“…In particular, along with various physical side effects, emotional and social problems, such as anxiety, depression, fear, loneliness, and hopelessness, may be experienced as a result of long-term treatment and uncertainty. [2,3] Among these, anxiety is one of the most common symptoms. The incidence of anxiety in cancer patients is >50%, and approximately 30% of the patients suffer from chronic anxiety.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Some studies have reported the use of music therapy before treatment [3,22], some before and during treatment [21], some only during treatment [28,29], and some over the course of treatment on patient's demand. [2,30] In the present study, we preferred administering music therapy to patients during radiotherapy.…”
Section: %639mentioning
confidence: 99%
See 1 more Smart Citation